2014
DOI: 10.15376/biores.9.3.4873-4887
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterisation of a Pectinolytic Enzyme from Paenibacillus xylanolyticus

Abstract: Pectinolytic enzymes play an important role in the processing of lignocellulosic materials because of their ability to improve the access of cellulases to their substrate by removing pectins. The strain Paenibacillus xylanolyticus 2-6L3 was isolated from mature compost obtained from agroindustrial wastes, and the enzyme pectate lyase from P. xylanolyticus 2-6L3, named PaenxylPel, was partially purified and subjected to structural and functional characterisation. The enzyme exhibited an optimum temperature betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The previous reports have shown that alkaline pectinase are mostly produced by bacteria especially Bacillus species (Kumar and Sharma 2012 ; Sonnotel and Nigam 2002 ; Sonia Ahlawat et al 2008 ). The pectinase enzyme from Bacillus pumilus dcsr1, Bacillus stearothermophilus , Paenibacillus xylanolyticusm , Bacillus halondurans M29 were shown to be active at high temperature and pH (Sharma and Satyanarayan 2006 ; Karbassi and Vaughn 1980 ; Giacobbe et al 2014 ; Mei et al 2013 ). This thermostability may be attributed to the cystein residue present in the amino acid sequence as observed in pectinase from Bacillus licheniformis (Singh et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous reports have shown that alkaline pectinase are mostly produced by bacteria especially Bacillus species (Kumar and Sharma 2012 ; Sonnotel and Nigam 2002 ; Sonia Ahlawat et al 2008 ). The pectinase enzyme from Bacillus pumilus dcsr1, Bacillus stearothermophilus , Paenibacillus xylanolyticusm , Bacillus halondurans M29 were shown to be active at high temperature and pH (Sharma and Satyanarayan 2006 ; Karbassi and Vaughn 1980 ; Giacobbe et al 2014 ; Mei et al 2013 ). This thermostability may be attributed to the cystein residue present in the amino acid sequence as observed in pectinase from Bacillus licheniformis (Singh et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic Assays : PG Activity : Polygalacturonase (PG) activity was assayed for 15 min with a 0.2% solution of polygalacturonic acid. The number of reducing groups, expressed as galacturonic acid released by enzymatic action was quantified by the DNS reagent assay and monitored by the absorbance of resulting colored mixture at 540 nm . One unit (U) of PG activity was defined as the amount of enzyme releasing 1 µmol of galacturonic acid per min under assay conditions.…”
Section: Methodsmentioning
confidence: 99%
“…DNA (approximately 50 ng) was amplified with the primers FD1 (5'-AGA GTT TGA TCC TGG CTC AG-3') and RD1 (5'-AAG GAG GTG ATC CAG CC-3') using a PCR mixture employed as previously described [14]. The PCR conditions were as described by Giacobbe et al [15]. Amplicons were purified using a QIAquick Gel Extraction kit (Qiagen S.p.A., Milan, Italy), and eluted DNAs were quantified and sequenced as previously reported [16].…”
Section: Isolation and Identification Of Bacterial Strainsmentioning
confidence: 99%
“…The bottles were sealed with stainless steel headpiece caps and sterile venting filters to insufflate CO 2 , if necessary, before starting the experiment. Experiments were either conducted on standard MH medium or on a modified medium containing MH salts, supplemented with yeast extract (5, 1, or 0 g/L) and polypeptone (15,10 or 0 g/L) and in which glucose was replaced by A. donax hydrolysate. A. donax hydrolysate was diluted to achieve the desired starting concentration of sugars.…”
Section: Optimization and Scale-up Of Sa Production In Shake Flasks Amentioning
confidence: 99%